Geotecnologias e Diagnóstico do Potencial da Agricultura Urbana e Periurbana no Âmbito Municipal de Jaboticabal, São Paulo, Brasil - Leticia Faria; David Luciano Rosalen; Ana Carolina Roque Cardoso; Laura de Oliveira (Confins)
Urban and Peri-Urban Agriculture (UPA) can contribute to absorbing a portion of the idle population by leveraging local and/or regional rural traditions, thereby enabling income generation and, most importantly, providing access to fresh and healthy food, contributing to Food Security and green spaces. For the appropriate implementation of UPA projects, Geotechnologies play a particularly prominent role, as they directly support the collection, representation, and management of georeferenced data. This study investigates the practice of Urban Agricultural Practices (UPA) in the city of Jaboticabal, São Paulo, which has a predominantly agricultural economy, particularly in the sugarcane sector and peanut cultivation. The municipality, with a population of approximately 24,204 residents (IBGE, 2017), has 31.5% of its population employed in the agricultural sector, which accounts for 50% of the ICMS revenue, with 40% coming from sugar and alcohol production. The research utilizes methodologies based on previous studies and open-source software tools, such as QGIS, to map existing and potential areas for UPA. The results indicate that vacant lots and public areas are promising spaces for the development of urban agricultural practices, contributing to improved quality of life and waste management. Jaboticabal master plan emphasizes the importance of sustainable production and the diversification of economic activities, reinforcing the relevance of UPA for the municipality.